To solve the proportion, we need to set the two ratios equal to each other and then cross multiply.
Let x be the unknown value we are looking for.
6/(5√11 - 6/5) = 5/(6√11 - 6/5)
Cross multiplying:
6(6√11 - 6/5) = 5(5√11 - 6/5)
36√11 - 36/5 = 25√11 - 6/5
Adding 36/5 to both sides:
36√11 = 25√11
Dividing by √11:
36 = 25
Since the equation is not true, there is no solution to this proportion.
Solve the proportion.%0D%0A%0D%0A%0D%0A(1 point)%0D%0AResponses%0D%0A%0D%0A%0D%0AImage with alt text: 6 over 5 square root 11 – 6 over 5%0D%0A%0D%0A%0D%0AImage with alt text: 5 over 6 square root 11 – 6 over 5%0D%0A%0D%0A%0D%0AImage with alt text: 5 over 6 square root 11 + 6 over 5
1 answer